2022
DOI: 10.1002/jia2.25900
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of active tuberculosis among people living with HIV receiving long‐term antiretroviral therapy in high TB/HIV burden settings in Thailand: implication for tuberculosis preventive therapy

Abstract: Introduction Among high tuberculosis (TB) and HIV burden countries in Asia, tuberculosis preventive therapy (TPT) in people living with HIV (PLWH) has been underutilized despite its proven benefits independent of antiretroviral therapy (ART). Therefore, we determined the incidence of active TB and mortality among 9179 adult PLWH who attended and received ART from 15 tertiary care hospitals across Thailand. Methods A retrospective study was conducted in 2018 using follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
2
4
1
Order By: Relevance
“…The results of the present study revealed that patients diagnosed with TB/HIV coinfection were on average 9.54 years younger than other patients. This finding is consistent with the results of a study by Suwanpimolkul et al Moreover, the average age of HIV-positive patients when starting antiretroviral treatment in coinfection with TB was reported to be lower than other patients without coinfection [ 34 ], which may suggest that the presence of one disease accelerates the progression of another disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study revealed that patients diagnosed with TB/HIV coinfection were on average 9.54 years younger than other patients. This finding is consistent with the results of a study by Suwanpimolkul et al Moreover, the average age of HIV-positive patients when starting antiretroviral treatment in coinfection with TB was reported to be lower than other patients without coinfection [ 34 ], which may suggest that the presence of one disease accelerates the progression of another disease.…”
Section: Discussionsupporting
confidence: 92%
“…Patients diagnosed with TB/HIV coinfection had lower weight compared to other TB patients, which is in line with the findings of another study that investigated the occurrence of active tuberculosis among HIV-infected patients [ 34 ]. This may suggest that the presence of both TB and HIV exacerbates the progression of these diseases.…”
Section: Discussionsupporting
confidence: 87%
“…In the United Kingdom (UK), the incidence rate of tuberculosis among people receiving HIV care at UK Collaborative HIV Cohort sites was 1.3 per 1000 person-years [ 20 ] and 2.81 cases per 1000 patient-years in tuberculosis-low prevalence settings [ 21 ]. The tuberculosis incidence rate was 4.1 per 100 patient-year in Brazil [ 22 ] and 750 per 100,000 persons-years in Thailand [ 23 ]. In high or intermediate tuberculosis burden settings, the incidence rate of tuberculosis was 4.17 per 100 person-years, whereas in low-burden settings, it was 0.4 per 100 person-years [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of TB preventive therapy (TPT) to antiretroviral therapy has been shown to reduce TB incidence by 30% and mortality by 35% to 50%. [ 25 ] The recommended regimens for treating HIV complicated with latent TB include the administration of rifapentine and isoniazid once a week for 12 weeks, rifampicin daily for 4 months, or isoniazid and rifampicin daily for 3 months. Recommended alternatives are daily treatment with isoniazid for 6 or 9 months or daily treatment with rifapentine and isoniazid for 1 month.…”
Section: Preventive Treatment Of Tbmentioning
confidence: 99%
“…[23] That is, a strategy of rapid antiretroviral therapy (ie, ART should be started within 7 days) should be implemented regardless of the CD4 + T-cell count. [24,25] Also, studies have shown that combination therapy with ART and anti-TB drugs is generally well tolerated. Early ART initiation allows for rapid immune recovery and reduces the risk of other opportunistic infections and all-cause mortality for people with HIV-TB co-infection.…”
Section: Treatmentmentioning
confidence: 99%